Hungary : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Hungary. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation discusses that in an increasingly uncertain global economic environment, Hungary's growth registered one of the highest rates in Europe in 2018. The economy now appears to be running above capacity and wages are growing rapidly amid historically low unemployment. It is thus likely that growth will slow down over the medium term. Supply-side reforms can help sustain the momentum. Policies have reduced vulnerabilities substantially; however, measures to support the targeted fiscal consolidation could be more ambitious to ensure that room for fiscal policy manoeuvre is rebuilt. Wages outstripping labor productivity growth, slower export growth, and shortcomings in the business environment for small and medium enterprises call for invigorating structural reform efforts. Improvements in competitiveness are needed to sustain rapid income convergence and address demographic challenges. The government's competitiveness program contains important elements. Focus should be on improving the business environment, enhancing the legal and regulatory framework, and increasing labor force participation.